Condicionamento neotectônico na rede de drenagem e no relevo do baixo curso do rio Doce (Espírito Santo, Sudeste do Brasil - Busato, Cirla (2020)
ABSTRACT The main objective of this research was to investigate the relationship of relief and drainage network with neotectonic mechanisms in the low course of the Doce River (Espírito Santo - southeastern Brazil). The methodological basis used was inte